Water quality monitoring, modelling and management for a catchment/reservoir system (Kranji phase I) - Wang, Jing Yuan. (2010)
The main objective of this project is to develop an integrated model for simulation and prediction of water quality in a tropical reservoir and catchment system, with emphasis on eutrophication, suspended solids and to a lesser extent, emerging trace organic contaminants. The integrated water quality/quantity model developed is useful to track the transport, quantity, quality and fate of water within a reservoir/catchment system. Such a model can then be used to assist management to enhance water quality in existing reservoirs and in planning of water resources by predicting the impacts of future land use changes or environmental perturbations. The integrated model developed is then applied on Kranji reservoir/catchment system. The scope of the study includes: (1) Development of an integrated 3D water quality reservoir model coupling the major biological, chemical and physical processes in both the reservoir water column and sediments. The Reservoir Model will mainly address the problems of eutrophication and the dissolved oxygen balance. (2) Development of rainfall-runoff quantity-quality models (Catchment models) to predict the source loads and flow rates from the contributing catchment areas feeding into the reservoir. (3) Field monitoring of the physical, chemical and biological parameters to establish baseline conditions in the reservoir and surrounding catchment, and for calibration and verification of the models developed. (4) Laboratory studies to establish the processes and associated kinetic coefficients underlying the important biological and chemical processes occurring in the reservoir. These coefficients are necessary for model developments.